On a Connection Between the Discrete Fractional Laplacian and Superdiffusion - Lizama-Yanez, C (Elsevier Ltd, 2015)
Abstract We relate the fractional powers of the discrete Laplacian with a standard time-fractional derivative in the sense of Liouville by encoding the iterative nature of the discrete operator through a time-fractional memory term. © 2015 Elsevier Ltd.